A high neutrophil to lymphocyte ratio is associated with poor nutritional status in chronic kidney disease patients. Issue 10 (28th November 2022) - Han, Qianqian; Lin, Shumin; He, Fengyi; Zhang, Rui; Xie, Xuefeng; Qing, Fengchu; Huang, Rong; Chen, Chaogang; Yang, Qiongqiong
Abstract: We aimed to investigate the relationship between the neutrophil to lymphocyte ratio (NLR) and nutritional parameters in chronic kidney disease (CKD) patients. In this cross-sectional study, 187 non-dialysis CKD patients were enrolled. Daily dietary energy intake (DEI) and daily dietary protein intake (DPI) were assessed by 3-d dietary records. Protein-energy wasting (PEW) was defined as Subjective Global Assessment (SGA) class B and C. Spearman correlation analysis, logistic regression analysis and receiver operating characteristic (ROC) curve analysis were performed. The median NLR was 2·51 (1·83, 3·83). Patients with CKD stage 5 had the highest NLR level. A total of 19·3 % ( n 36) of patients suffered from PEW. The NLR was positively correlated with SGA and serum P, and the NLR was negatively correlated with BMI, waist and hip circumference, triceps skinfold thickness, mid-arm muscle circumference, DPI and Hb. Multivariate logistic regression analysis adjusted for DPI, DEI, serum creatinine, blood urea nitrogen, uric acid and Hb showed that a high NLR was an independent risk factor for PEW (OR = 1·393, 95 % CI 1·078, 1·800, P = 0·011). ROC analysis showed that an NLR ≥ 2·62 had the ability to identify PEW among CKD patients, with a sensitivity of 77·8 %, a specificity of 62·3 % and an AUC of 0·71 (95 % CI 0·63, 0·81, P < 0·001). The NLR was closely associated with nutritional status. NLR may be an indicator of PEW in CKD patients.